PEG-conjugated bovine haemoglobin enhances efficiency of chemotherapeutic agent doxorubicin with alleviating DOX-induced splenocardiac toxicity in the breast cancer - Bingting Li; Jun Zhang; Ning Ma; Weidan Li; Guoxing You; Gan Chen; Lian Zhao; Quan Wang; Hong Zhou (Artificial Cells, Nanomedicine, and Biotechnology)
Doxorubicin (DOX) is an effective chemotherapeutic agent widely used for cancer treatment. However, hypoxia in tumour tissue and obvious adverse effects particularly cardiotoxicity restricts the clinical usage of DOX. Our study is based on the co-administration of haemoglobin-based oxygen carriers (HBOCs) and DOX in a breast cancer model to investigate HBOCs’ ability to enhance chemotherapeutic effectiveness and its capabilities to alleviate the side effects induced by DOX. In an in-vitro study, the results suggested the cytotoxicity of DOX was significantly improved when combined with HBOCs in a hypoxic environment, and produced more γ-H2AX indicating higher DNA damage than free DOX did. Compared with administration of free DOX, combined therapy exhibited a stronger tumour suppressive effect in an in-vivo study. Further mechanism studies showed that the expression of various proteins such as hypoxia-inducible factor-1α (HIF-1α), CD31, CD34, and vascular endothelial growth factor (VEGF) in tumour tissues was also significantly reduced in the combined treatment group. In addition, HBOCs can significantly reduce the splenocardiac toxicity induced by DOX, according to the results of the haematoxylin and eosin (H&E) staining and histological investigation. This study suggested that PEG-conjugated bovine haemoglobin may not only reduce the hypoxia in tumours and increase the efficiency of chemotherapeutic agent DOX, but also alleviate the irreversible heart toxicity caused by DOX-inducted splenocardiac dysregulation.